Catalytic Cyclohexane Oxidation In The Presence Of Alcohols Of Different Nature - Suprun, Oleksandr; Reutskyy, Viktor; Ivashchuk, Oleksandr; Mudryy, Sergiy (Видавництво Львівської політехніки, 2013)
Quantitative and qualitative influence of binary catalytic systems [cobalt naphthenate – alcohol] in liquidphase homogeneous-catalytic oxidation of cyclohexane was considered.
Keywords: cyclohexane; oxidation; catalysis; catalytic systems